The burden of vaccine-preventable invasive bacterial infections and pneumonia in children admitted to hospital in urban Nepal - Kelly, Dominic F.; Thorson, Stephen; Maskey, Mitu; Mahat, Sandeep; Shrestha, Umesh; Hamaluba, Mainga; Williams, Eleri; Dongol, Sabina; Werno, Anja M.; Portess, Howard; Yadav, Bharat K.; Adhikari, Neelam; et al. (International journal of infectious diseases, 2011)
Protein–polysaccharide vaccines have made a significant impact on the burden of disease caused by encapsulated bacteria such as Streptococcus pneumoniae, Haemophilus influenzae, Neisseria meningitidis, and have the potential to do so for Salmonella Typhi. Nepal is one of many resource-poor nations with limited information on the epidemiology of childhood infections caused by these pathogens. Over a 21-month period, we studied children aged ≤12 years admitted to an urban hospital in Nepal with suspected bacteremia, meningitis, or pneumonia. Patan Hospital is a non-profit hospital with the second largest pediatric unit in the Kathmandu Valley. Of 2039 children enrolled in the study, 142 (7.5%) included in the analysis had positive blood cultures. The agents of enteric fever, Salmonella Typhi and Salmonella Paratyphi, accounted for 59/142 (42%) of all bacteremias and were the most frequently cultured pathogens in children ≥1 year of age. S. pneumoniae was isolated in 16% of positive blood cultures and was the most common cause of bacteremia in children <1 year of age. Pneumonia accounted for 51% of admissions in children ≥2 months, with 44% of these children having radiographically defined primary endpoint pneumonia. S. pneumoniae was the most commonly identified pathogen in cases of pneumonia and meningitis. The S. pneumoniae serotype distribution indicated that the 10-valent and 13-valent pneumococcal conjugate vaccines would cover 44% and 47%, respectively, of all S. pneumoniae cultured from blood or cerebrospinal fluid (CSF) isolates and 62% and 67%, respectively, of isolates associated with pneumonia. H. influenzae type b was isolated infrequently from blood or CSF cultures, but is likely to be more important as a cause of pneumonia. The data on the burden of invasive bacterial infections and pneumonia from this study suggest that vaccines in development against Salmonella Typhi and the pneumococcus have the potential to significantly improve the health of children in Nepal.